Conceptualising minimum core obligations under the right to health: How should we define and implement the 'morality of the depths'. Issue 4 (18th May 2016) - Forman, Lisa; Caraoshi, Luljeta; Chapman, Audrey R.; Lamprea, Everaldo
Abstract : To prevent progressive realisation within resources from undermining both domestic and international responsibilities towards health, international human rights law institutions developed the idea that these rights hold an inviolable 'core' equivalent to essential health needs. Yet few aspects of this right and indeed of economic social and cultural rights have generated greater debate and unresolved questions than the core concept: Is the core fixed or moveable, non-derogable or restrictable, universal or country-specific? Is its function to guarantee specified bundles of the most essential health facilities, goods and services, or it is to require governments to act reasonably to progressively realize these minimal health entitlements? Is the concept legitimate in terms of international law? And what are acceptable methods to further develop the content of these entitlements and duties? This paper seeks to address several of these questions in light of the evolution of this concept in international law and human rights scholarship, focusing in particular on the development of core obligations in relation to the right to health.